Intermultiplet transitions and magnetic long-range order in Sm-based pyrochlores - Peçanha-Antonio, V; Feng, E; Sun, X; Adroja, D; Walker, H; Gibbs, A; Orlandi, F; Su, Y; Brückel, T (American Physical Society, 2019)
We present bulk and neutron scattering measurements performed on the isotopically enriched Sm2Ti2O7154 and Sm2Sn2O7154 samples. Both compounds display sharp heat capacity anomalies, at 350 and 440 mK, respectively. Inelastic neutron scattering measurements are employed to determine the crystalline electric field (CEF) level scheme, which includes transitions between the ground-state and first excited J multiplets of the Sm3+ ion. To further validate those results, the single-ion magnetic susceptibility of the compounds is calculated and compared with the experimental dc-susceptibility measured in low applied magnetic fields. It is demonstrated that the inclusion of intermultiplet transitions in the CEF analysis is fundamental to the understanding of the intermediate and, more importantly, low-temperature magnetic behavior of the Sm-based pyrochlores. Finally, the heat capacity anomaly is shown to correspond to the onset of an all-in-all-out long-range order in the stannate sample, while in the titanate a dipolar long-range order can be only indirectly inferred.